PENGARUH RATING DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PRODUK PAKAIAN PADA MARKETPLACE SHOPEE (STUDI KASUS MAHASISWA UNIVERSITAS AL-WASHLIYAH LABUHANBATU) - Ayla Siregar; Muhammad Irwansyah Hasibuan; mhd amin; Junaidi Mustapa Harahap; Salsabila Pramudistya Elvisyahfri (Politeknik Bisnis Indonesia, 2022)
This study aims to determine the effect of ratings and online customer reviews purchasing decisions online on Marketplace , a case study on Al-Washliyah Labuhanbatu University students. The method used is a quantitative method. The sample used was 79 respondents who had used the Shopee application to shop online. The technique used is non-probability sampling by distributing questionnaires. The data analysis technique in this study is the classical assumption test, multiple linear regression, the coefficient of determination. The partial test results show that the Rating variable (X1) and the Online Customer Review (X2) have a positive and significant effect on the Purchase Decision variable (Y). The t value2.066 the variable X1 and the t value for thecount variable X2 is 3.915 while the ttable 1.992 (tis > ttable). The simultaneous test results show that variable X1 and variable X2 have a positive and significant effect on the Purchase Decision variable (Y). The fcount value is 17.992 and the ftable (fcount > ftable). The test results for the coefficient of determination show that the R Square value is 0.667, meaning that all X variables contribute 66.7% to Y. While the remaining 33.3% is explained by other factors outside of this study. Keywords: Rating, Online Customer Review, Purchase Intention.